Artificial intelligence in packaging design: integrating traditional Chinese cultural elements for cultural preservation and innovation - Wang, Hang; Alli, Hassan; Hawari, Nurhanisah; Wenyu, Wang (Human Resource Management Academic Research Society, 2024)
The integration of artificial intelligence (AI) into packaging design has transformed the industry by enabling personalization, interactivity, and efficiency. Simultaneously, traditional Chinese cultural elements, such as motifs, symbols, and colors, hold significant value in preserving heritage and fostering emotional connections with consumers. This study explores the intersection of domains and analyzing the AI technologies that can support the Chinese traditional cultural aesthetics packaging for fulfilling the modern consumer demands. By examining existing literature, case studies, and conceptual frameworks, it can indicate several key challenges and overcoming toward commercialization as well as highlighting the opportunities for sustainability and cross-cultural innovation. The findings underscore the potential of AI to balance the tradition and modernity of a new packaging design and offering a new pathway to enhance the consumer preference, preserve cultural heritage, and achieving the global market needs.